Analysis of Free Phenols from Two Varieties of Vitis vinifera in Different Geographical Origins - Xinjie, Zhao; Jingxia, Mu; Jianmin, Liu; Yufeng, Wang; Chuanyan, Sun (Asian Journal of Chemistry, 2010)
Two grape (Vitis vinifera) varieties such as Cabernet sauvignon and Cabernet gernischet collected from two different geographical origins (Penglai of Shandong Province and Changli of Hebei Province) were used for analysis of gallic acid, catechin, epicatechin and epigallocatechin, contents of these compounds were investigated by HPLC (high performance liquid chromatography). The results showed that the phenolic compounds were different in the same variety from different areas (p < 0.05)). The content of catechin was the highest among these varities and the contents of other compounds were catechin > epigallocatechin > epicatechin > gallic acid.